2021
DOI: 10.1536/ihj.20-788
|View full text |Cite
|
Sign up to set email alerts
|

How to Estimate the Optimal Heart Rate in Patients with Heart Failure with Preserved Ejection Fraction

Abstract: Ideal heart rate (HR), particularly for those with heart failure with preserved ejection fraction (HFpEF), remains unknown. We hypothesized that cardiac output would be maximum when the overlap between E-wave and A-wave at the trans-mitral flow is "zero" in the Doppler echocardiography. We retrospectively investigated the association among the overlap length between two waves, actual HR, and other echocardiographic parameters to construct a formula for estimating theoretically ideal HR among those with HFpEF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our team recently found that a "zero" overlap between E wave and A wave in the trans-mitral echocardiography flow was associated with maximum cardiac output and greater clinical outcomes in patients with systolic heart failure [7]. We expanded this concept and proposed formulas to estimate optimal HR using deceleration time alone for those with preserved ejection fraction (HFpEF) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Our team recently found that a "zero" overlap between E wave and A wave in the trans-mitral echocardiography flow was associated with maximum cardiac output and greater clinical outcomes in patients with systolic heart failure [7]. We expanded this concept and proposed formulas to estimate optimal HR using deceleration time alone for those with preserved ejection fraction (HFpEF) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with diastolic dysfunction, the optimal heart rate might be relatively high, and aggressive beta-blocker therapy might reduce cardiac output. 10 The optimal medical therapy following the recovery of the LVEF, as found in our patient, also remains a future concern. Patisiran, which is currently used only for hereditary cardiac ATTR, might be more useful to achieve reverse remodeling than tafamidis.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of pulmonary congestion is associated with a significantly increased risk of cardiovascular mortality and morbidity in patients with acute-on-chronic heart failure [2]. The recent literature has shown that persistent elevations of ReDS values during index hospitalization were associated with a higher risk of all-cause death and incident heart failure hospitalization [12]. A previous retrospective study demonstrated that the post-discharge immediate measurement of ReDS values and medication adjustment was associated with a lower risk of 30-day cardiovascular admission [8].…”
Section: Prognostic Impact Of Reds-guidingmentioning
confidence: 99%